2013
DOI: 10.1097/iae.0b013e31827e247b
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Intravitreal Implant for Treatment of Uveitic Persistent Cystoid Macular Edema in Vitrectomized Patients

Abstract: In this small case series of eyes with limited follow-up, treatment with dexamethasone intravitreal implant injection for uveitic macular edema in vitrectomized eyes was associated with favorable visual outcomes and had an acceptable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 16 publications
4
29
0
1
Order By: Relevance
“…Average CME duration prior to injection was 12 months. Changes in CMT were comparable to our study [31]. Our study did not include vitrectomized eyes.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Average CME duration prior to injection was 12 months. Changes in CMT were comparable to our study [31]. Our study did not include vitrectomized eyes.…”
Section: Discussionsupporting
confidence: 72%
“…There is little evidence in the published literature of the effect of DEX-DDS in the treatment of edema persisting following other treatments [28,29,30,31,32,33]. The purpose of our study was to examine the effect of DEX-DDS in patients with severely recalcitrant CME that had a poor or short-term response to other treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…50 Among studies with patients having a mix of single or multiple implants and macular oedema, significant improvements in central retinal thickness were reported up to 12 months in one study, 50 with another study reporting significant improvements at 3 months but not at 6 months. 85 In terms of repeat implants, one study reported that after the second implant BCVA improved significantly by 1 month but then decreased, with a similar trend following up to six implants (not significant but small patient numbers). 18 Central retinal thickness and VH also showed a significant temporary improvement after the second implant, with similar (non-significant) improvements after the third and fourth implants.…”
Section: Dexamethasone Studiesmentioning
confidence: 99%
“…18,50,51,[79][80][81][82][83][84][85][86] This is based on data from the company submission for DEX; 43 the original study publications have not been examined because of time constraints. These data are included here as they provide some data on repeat implants, implants in both eyes and corticosteroid reduction, which were not assessed in the HURON trial.…”
Section: Dexamethasone Studiesmentioning
confidence: 99%
“…25 Using a slow-release DXM implant (Ozurdex), a complete resolution of the vitreous inflammation has been observed after 6 months in 47% of 77 uveitis patients with an initial vitreous Tyndall effect of at least 1.5+. 26 A significant improvement in persistent inflammatory ME has been shown in terms of centrofoveal thick ness 27 and VA in more than 85% of patients at 4 months. 28 The efficacy duration may differ and a median time to recurrence is 5 months.…”
Section: Corticosteroidsmentioning
confidence: 99%